Utilization of Seawater for Pineapple Cultivation - Yufdy, Muhammad Prama (2004)
Pineapple needs a large amount of potassium (350 kg K ha-1), which is higher than the other nutrient requirements. As a crassulacean acid metabolism species, it also requires some amount of Na as a beneficial nutrient to replace part of potassium’s function. This provides an opportunity to decrease K fertilizer cost, especially for non-K fertilizer producer countries such as Malaysia where the import bill for K fertilizer is the highest compared to N and P fertilizers. A readily available source of Na is seawater, which contains about 4,000-10,000 mg L-1 Na. Three experiments were conducted to study the possibility of utilizing nutrients from seawater. The first experiment was to observe sorption and desorption of K, Na, Ca and Mg from different concentrations of seawater in natural zeolite. The second and third experiments were to study the extent to which Na could replace the function of K in pineapple. The results indicated that natural zeolite could sorb Na, Mg and K from seawater. The highest sorption for Na, Mg and K was from 40% diluted seawater at 2260.00, 210.00 and 60.00 4g g-1 zeolite, respectively. The cations were then desorbed from zeolite cavities. As a slow release agent of cations, zeolite treated with 20% seawater released 576.67 and 102.33 4g g-1 zeolite of Na and Mg, respectively. Application of Na for K substitution (0, 15, 30 and 60%) from seawater and NaCl in a Bungor Series of Typic Paleudult soil resulted in no significant increase in soil pH, CEC, EC and turbidity. Sodium uptake in D-leaf increased significantly up to 30% Na for K substitution (diluted seawater) and 60% Na for K substitution (NaCl) without any toxic effect to the plant. The highest plant dry weight (3.45 kg) was obtained from 30% Na for K substitution using diluted seawater. However, there was no significant difference among all treatments for fresh fruit weight. Similar results in soil properties and Na uptake were also found in a more detailed study conducted in a Seremban Series of Plintic Kandiudult soil. Application of diluted seawater, NaCl, and seawater-zeolite effluent decreased plant dry weight which can be attributed to decreasing cell membrane stability as an indication of toxicity due to increasing Na in plant tissue for 60% Na for K substitution. However, sodium application induces thicker water storage tissue in D-leaf, which may be an adaptation response of pineapple to increased Na. In general, the results of the study indicated that zeolite can sorb and desorb Na, Mg and K; and 30% of pineapple K requirement (in term of fertilizer application) can be replaced by Na from diluted seawater, NaCl, zeolite saturated with seawater and seawater-zeolite effluent, and the rest (70%) from K fertilizer.